Innate Immune Response to House Dust Mite Allergens in Allergic Asthma - Winna Soleha; Febriana Catur Iswanti (Molecular and Cellular Biomedical Sciences, 2021)
Asthma is a major health problem and one of the leading causes of death in the world. The prevalence of asthma in Indonesia is high, with a recurrence >50%. Allergic sensitization in asthma is mainly caused by house dust mite (HDM) allergens, both from the mite’s body and its contaminants (e.g., lipopolysaccharides). HDM allergens stimulate several pathways in the innate immune response based on the HDM allergen groups that sensitize them. The innate immune response to HDM allergen exposure occurs when pattern recognition receptors (PRRs) recognizes the allergen, thereby stimulating respiratory epithelial cells to release cytokines, namely, thymic stromal lymphopoietin (TSLP), interleukin-25 (IL -25), and IL-33. The release of IL-25 and IL-33 activates group 2 innate lymphoid cells (ILC2) to release Th2-type cytokines (i.e., IL-5 and IL-13), resulting in allergic airway inflammation via IgE secretion by B cells, recruitment of eosinophils, and respiratory tract remodeling. Dendritic cells induce an adaptive immune response through Th2 activation in the sensitization and effector phases. Other mediators that contributed to the innate immune response include C-C motif chemokine ligand 20 (CCL-20) and granulocyte-macrophage colony-stimulating factor (GM-CSF). A deeper understanding of the components and mechanisms involved in innate immunity against HDM allergens creates the potential to develop alternative therapeutic targets for allergic asthma treatment.Keywords: house dust mite allergens, innate immunity, allergic asthma, respiratory epithelium, inflammatory cytokines